2014
DOI: 10.1002/2013wr014984
|View full text |Cite
|
Sign up to set email alerts
|

A streamline splitting pore‐network approach for computationally inexpensive and accurate simulation of transport in porous media

Abstract: Several approaches have been developed in the literature for solving flow and transport at the pore scale. Some authors use a direct modeling approach where the fundamental flow and transport equations are solved on the actual pore-space geometry. Such direct modeling, while very accurate, comes at a great computational cost. Network models are computationally more efficient because the pore-space morphology is approximated. Typically, a mixed cell method (MCM) is employed for solving the flow and transport sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…The latter's usage however is preferred to be limited for cost efficiency if a reliable network model is verified. We note that the solute transport algorithm (i.e., MCM) has been extensively compared to both experimental data and other numerical simulation methods, such as the streamline splitting method of Mehmani et al [2014], the Superposing Transport Method of Mehmani [2014], and CFD simulations. In Mehmani [2014], comparisons with experimental data for longitudinal dispersion coefficient available from the literature for unconsolidated bead packs show that the method is in general agreement with these data for the Peclet numbers considered in this work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter's usage however is preferred to be limited for cost efficiency if a reliable network model is verified. We note that the solute transport algorithm (i.e., MCM) has been extensively compared to both experimental data and other numerical simulation methods, such as the streamline splitting method of Mehmani et al [2014], the Superposing Transport Method of Mehmani [2014], and CFD simulations. In Mehmani [2014], comparisons with experimental data for longitudinal dispersion coefficient available from the literature for unconsolidated bead packs show that the method is in general agreement with these data for the Peclet numbers considered in this work.…”
Section: Discussionmentioning
confidence: 99%
“…The MCM transport equation (given by equation (3)) is formulated by imposing species balance on each pore and assuming the solute is perfectly mixed at the pores. The implications of this mixing assumption are discussed in Mehmani et al [2014], but are not thought to be of primary importance in this study (considering: the nature of our study is on the qualitative side, microporous portions of the pore-scale domains promote diffusive mixing, and the disordered nature of the medium itself demotes any macroscopic effects arising from the mixing assumption as discussed …”
Section: 1002/2015wr016948mentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to accurately capture partial mixing within pores and shear dispersion within throats, Mehmani et al (2014) and Mehmani (2014) developed two pore-network models, respectively: the streamline splitting method (SSM) and superposing transport method (STM). These models were developed with the aim of exploring the possibility of capturing the porescale physics discussed above under an Eulerian framework.…”
Section: Network Modeling Of Solute Transportmentioning
confidence: 99%
“…After all, modeling efforts should ideally seek ultimate simplicity while disposing of unnecessary complexity. Mehmani et al (2014) showed that the impact of pore-level mixing assumptions, partial vs. perfect, is very signifi cant in ordered media (e.g., micromodels), but comparatively insubstantial in 3-D disordered granular media (e.g., sandstones). In fact, the average difference between the concentration fi elds obtained via SSM and the relatively less accurate MCM for disordered granular media was ~6% of the maximum concentration value (although the impact on upscaled transverse dispersion coeffi cients is yet to be studied).…”
Section: Network Modeling Of Solute Transportmentioning
confidence: 99%